Anti-Brucella activity of Caryopteris mongolica Bunge root extract against Brucella melitensis infection in mice - Tsevelmaa N; Narangerel B; Odgerel O; Dariimaa D; Batkhuu J (BMC, 2018)
Abstract Background The current treatment for human brucellosis requires a combination of antibiotics for long periods of time, and the reported incidence and prevalence of the disease vary widely in nomadic livestock of Mongolia. The objective of the present study was to evaluate the in vivo antibacterial activity of the C. mongolica root extract against B. melitensis. Methods In this study, we used of 6 groups of mice (n = 5). Five groups of BALB/c mice were inoculated intraperitoneally with the M16 strain of B. melintensis, as follows: (i) one group was used for pretreatment monitoring; (ii) the control group was administered 2% Tween 80 and was used as the non-treatment group; and the other three groups were treated with one oral gavage per day for 21 days with (iii) doxycycline (2 mg/day), (iv) doxycycline (1 mg/day) with root extract (20 mg/day), and (v) C. mongolica root extract (20 mg/day). The one group that was kept non-infected was used as a healthy control group. Results This study demonstrated that daily treatment with doxycycline alone and in combination with C. mongolica root extract significantly reduced splenic infection at the end of treatment. However, the spleen index of both the doxycycline-treated and the combination-treated groups of mice decreased by approximately 50% compared to that of the healthy control mouse group. Treatment with the C. mongolica root extract resulted in a 1.47log reduction in splenic infection compared to the non-treatment group, and the spleen index of the C. mongolica-treated group of mice was the same as that of the normal mouse group. In all treatment groups, neutrophil phagocytic activity significantly decreased, and all treatment groups demonstrated splenic regeneration. Conclusions The present study showed that the C. mongolica root extract may be useful in the treatment of brucellosis patients, in combination with doxycycline or other antibiotics, to reduce the toxicity of high-dosage antibiotics, to prevent the development of antibiotic resistance and to prevent Brucella infection.